Human growth, behaviour and development essential theory and application in social work - Gibson, Alastair; Gibson, Neil (SAGE, 2016)
"Understanding the way in which individuals develop before birth, as babies, children and adolescents through to young and older adulthood towards death is an important part of any social work role. Being able to skillfully apply this understanding in real life practice situations is even more important, as purposeful translations of human development are at the heart of effective professional practice. Introducing students to emotional, psychological and social developmental theories of human growth before exploring in detail how these theories can be incorporated into practice, this book will ensure students have all the tools they need to not only understand but critically appraise and apply psychosocial theories early on in training and whilst on placement. With the help of real world case studies, summaries and tips for further study, it will show students how life course theories inter-relate and how they can make appropriate, purposeful translations of theory into skilled, professional practice."--Back cover.